Blessed be a Flowertown, U.S.A. adventure - Altergott, Rick 1961- (Fantagraphics Books, Inc., 2024)
When Tom "The Acid King" Cottonwood is sentenced to prison for dealing, he vows to exact revenge on the judge and all of Flowertown, U.S.A. One year later, when hillbilly Henry Hotchkiss violates the single principle binding the members of the local men's group, the 40 Acres Club -- preserving his virginity -- he proactively excommunicates himself to the woods in shame, prompting his distraught best friend, Doofus Anderssen (he of straw boater and Beatle haircut over a permanent five-o'clock shadow), to organize a community search. But little does he know that Cottonwood has been paroled and is making plans in those same woods to fulfill his destiny as "The Acid King" -- in the form of a deadly act of terrorism he calls "Scorpio Rising.
Keywords: Criminals / Comic books, strips, etc; Terrorism / Comic books, strips, etc; Comic books, strips, etc / United States; Small cities / Comic books, strips, etc; Graphic novels / United States; Criminels / Bandes dessinées; Terrorisme / Bandes dessinées; Humorous fiction; Underground comics; Comics (Graphic works); Graphic novels; Bandes dessinées; Comic